The Common Factors Model for Generalist Practice - Cameron, Mark; Keenan, Elizabeth King (Pearson Education, 2013)
Keywords: Social work administration; dept.swk; faculty_collection

Social work practice with gay men and lesbians within organizations - Appleby, G.A. (Foundations of Social Work Practice with Lesbian and Gay Persons, 2013)
The premise ofthis chapter is that U.S. society will reject continued attempts to defend discrimination against lesbian and gay people in the name of “family values? or “special rights? or “preservation ofmorale? or any other meaningless slogan. Such discrimination will be seen for what it really is: bigotry. However, social change is slow and discriminatory attitudes and behaviors will continue to be oppressive environmental and organizational influences on lesbian and gay social workers employed by human service agencies. This vestige of homophobia and heterosexism, therefore, must become the target of social work intervention (Appleby, 1995). © 1998 by The Haworth Press, Inc. All rights reserved.
Keywords: dept.swk

The effects of cumulative risk and protection on problem behaviors for youth in an urban school-based system of care - Whitson, Melissa L.; Bernard, Stanley; Kaufman, Joy S. (Community Mental Health Journal, 2013)
The present study examined the cumulative effects of risk and protective factors on internalizing and externalizing problems for a sample of youth who were diagnosed with a severe emotional disturbance and enrolled in an urban school-based system of care. The sample included 139 Latino and African American children (ages 5-19; 65 % male) and their families. After controlling for demographic variables, the results of hierarchical multiple regression analyses revealed that cumulative risk and protection were significantly related to internalizing problem behaviors, and cumulative protection was negatively related to externalizing problem behaviors. The findings support the importance of including or increasing strength building approaches, in addition to risk reduction, in order to maximize prevention and intervention efforts for system-of-care populations.
Keywords: Affective Symptoms; African American; African Americans; Child; Child, Preschool; Children's mental health; Cumulative protective factors; Cumulative risk factors; Female; Hispanic; Hispanic Americans; Humans; Internal-External Control; Internalizing and externalizing behavioral problems; Interviews as Topic; Male; Psychiatric Status Rating Scales; Questionnaires; Regression Analysis; Risk; Risk Factors; School Health Services; Schools; Severity of Illness Index; Social Behavior Disorders; Socioeconomic Factors; Systems of care; Urban Population; antisocial personality disorder; article; child; control; dept.swk; emotional disorder; female; human; interview; male; organization and management; peer-reviewed; preschool child; psychological aspect; psychological rating scale; questionnaire; regression analysis; risk; risk factor; school; school health service; severity of illness index; socioeconomics; statistics; urban population

Relationships between child emotional and behavioral symptoms and caregiver strain and parenting stress - Vaughan, Ellen L.; Feinn, Richard; Bernard, Stanley; Brereton, Maria; Kaufman, Joy S. (Journal of Family Issues, 2013)
Children with emotional and behavioral disturbance often have difficulties in multiple symptom domains. This study investigates the relationships between child symptoms and caregiver strain and parenting stress among 177 youth and their caregivers participating in a school-based system of care. Youth were grouped by symptom domain and included those with low scores on both internalizing and externalizing symptoms, those with only high internalizing symptoms, those with only high externalizing symptoms, and those with high symptoms levels in both internalizing and externalizing domains. Results revealed significant group differences on measures of caregiver strain and parenting stress. Caregivers of youth with symptoms in both internalizing and externalizing domains reported the highest levels of strain and stress; however, there was some variation in group differences by caregiver outcome. The results of this study emphasize the importance of providing not only services for youth but also support services for their caregivers.
Keywords: caregiver strain; dept.swk; parenting stress; peer-reviewed; serious emotional and behavioral disturbance

Cultivating curiosity: integrating hybrid teaching in courses in human behavior in the social environment - Rodriguez-Keyes, Elizabeth; Schneider, Dana A (Journal of Teaching in Social Work, 2013)
This study illustrates an experience of implementing a hybrid model for teaching human behavior in the social environment in an urban university setting. Developing a hybrid model in a BSW program arose out of a desire to reach students in a different way. Designed to promote curiosity and active learning, this particular hybrid model has students engage in weekly online activities between their weekly on-ground classes. This article reviews key pedagogical concerns and presents preliminary findings, including student feedback, instructor observations, and strategies for faculty interested in developing such courses. © 2013 Copyright Taylor and Francis Group, LLC.
Keywords: dept.swk; education; hybrid; online; peer-reviewed; social work; student perceptions; technology

Being known in undergraduate social work education: the role of instructors in fostering student engagement and motivation - Rodriguez-Keyes, Elizabeth; Schneider, Dana A; Keenan, Elizabeth King (Social Work Education, 2013)
Most undergraduate students pursue a social work major because of their desire to help others. Students tend to be more interested in doing than in understanding the research and knowledge of the profession and the complexities of social work practice. Instructors are often faced with the challenge of enhancing student motivation to learn challenging course material. This study explored student perceptions of instructor influences on their motivation and engagement in learning. Through online surveys, students described their experiences of being known and how those experiences affected their participation in practice, research, and human behavior in the social environment courses. Results showed that instructor caring (providing recognition, expressing relational qualities, and responding to students) positively influences student motivation and affective learning by increasing comfort, willingness to ask questions, take risks, and overall participation. Conversely, of those who reported mixed experiences or who felt unknown, most reported a negative impact on their motivation and participation. These findings suggest that social work faculty can influence student motivation and engagement with essential social work curriculum by expressing care and helping students feel known in the classroom. © 2013 Copyright Taylor and Francis Group, LLC.
Keywords: BSW Education; Being Known; Instructor Influence; Motivation; Student Engagement; dept.swk

The impact of a mental health crisis respite upon clients' symptom distress. - Rosen, Jonathan; O'Connell, Maria (Community mental health journal, 2013)
This study examined clients who were admitted to a mental health respite program in the first 3 months of 2011 in order to identify the ability of the program to reduce symptom distress and to explore related psychosocial factors. Participants were provided with self-report questionnaires that included measurements of demographics, mental health status, symptom severity, and program satisfaction. Results indicate a significant improvement in symptom distress (p < 0.05), mental health confidence (p < 0.1), and self-esteem (p < 0.05) from admission to discharge. No change was detected in largely external measurements.
Keywords: *Mental Disorders/pp [Physiopathology]; *Mental Disorders/th [Therapy]; Adult; Community Mental Health Services; Community mental health; Female; Hospital diversion; Humans; Male; Mental Disorders; Mental health respite; Middle Aged; Questionnaires; Surveys and Questionnaires; Symptom distress; United States; adult; article; dept.swk; evaluation study; female; human; male; mental disease; mental health service; middle aged; pathophysiology; peer-reviewed; questionnaire